2013
DOI: 10.1088/0004-637x/778/2/188
|View full text |Cite
|
Sign up to set email alerts
|

EMPIRICAL LINKS BETWEEN XRB AND AGN ACCRETION USING THE COMPLETEz< 0.4 SPECTROSCOPIC CSC/SDSS CATALOG

Abstract: Striking similarities have been seen between accretion signatures of Galactic X-ray binary (XRB) systems and active galactic nuclei (AGN). XRB spectral states show a V-shaped correlation between X-ray spectral hardness and Eddington ratio as they vary, and some AGN samples reveal a similar trend, implying analogous processes at vastly larger masses and timescales. To further investigate the analogies, we have matched 617 sources from the Chandra Source Catalog to SDSS spectroscopy, and uniformly measured both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 62 publications
(37 reference statements)
3
31
0
Order By: Relevance
“…Quite surprisingly, in the λ Edd − η jet plane, the CSOs from our sample occupy the same locus as "doublelobed" (i.e., Fanaroff-Riley type II) radio quasars, discussed in a similar context by, e.g., van Velzen & Falcke (2013), and more recently also Rusinek et al (2017). In order to illustrate this finding, in Figure 6, we plot all the sources from the Rusinek et al sample -including narrow-line radio galaxies, broad-line radio galaxies, and radio quasars -along with our targets (denoted in the figure by red squares; note that here on the y-axis we plot simply P j /L bol instead of η jet ).…”
Section: Jet Production Efficiency Parameterssupporting
confidence: 74%
See 1 more Smart Citation
“…Quite surprisingly, in the λ Edd − η jet plane, the CSOs from our sample occupy the same locus as "doublelobed" (i.e., Fanaroff-Riley type II) radio quasars, discussed in a similar context by, e.g., van Velzen & Falcke (2013), and more recently also Rusinek et al (2017). In order to illustrate this finding, in Figure 6, we plot all the sources from the Rusinek et al sample -including narrow-line radio galaxies, broad-line radio galaxies, and radio quasars -along with our targets (denoted in the figure by red squares; note that here on the y-axis we plot simply P j /L bol instead of η jet ).…”
Section: Jet Production Efficiency Parameterssupporting
confidence: 74%
“…1404+286 and 1511+0518, which curiously are also classified as Compton-thick based on the X-ray spectroscopy (Guainazzi et al 2004;Siemiginowska et al 2016;Sobolewska et al 2019a,b), the bolometric luminosities obtained as described above should be considered as not reliable, because they significantly underestimate the true radiative power of the AGN; the major source of the uncertainty here is the problem with extracting relatively weak narrow Hβ fraction from much more prominent broad components. For 1511+0518, we have therefore decided to use the L bol estimate following from the SED fitting by Trichas et al (2013), while for 1404+286 we used the scaling between the L bol and the 12 µm luminosity established for quasar sources by Richards et al (2006), utilizing the Infrared Astronomi- cal Satellite (IRAS) data (see Kosmaczewski et al 2019).…”
Section: Sdss Datamentioning
confidence: 99%
“…The anti-and positive correlations of Γ − LX/L Edd are found in both XRBs and a sample of AGNs, which are explained by the ADAF and disk-corona model respectively (e.g., Wang et al 2004;Shemmer et al 2006;Yuan et al 2007;Wu & Gu 2008;Markowitzet al 2009;Sobolewska & Papadakis 2009;Gu & Cao 2009;Emmanoulopoulos et al 2012;Trichas et al 2013;Plotkin et al 2013;Allen et al 2015;Yang et al 2015). The X-ray photon index, Γ, is regulated by the electron temperature, Te, and optical depth, τ , of the corona/ADAF (the so-called y-parameter, e.g., Zdziarski et al 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Wu & Gu (2008) performed a spectral study for XRBs in the decay of their outbursts and found that a transition between anti-and positive correlations of Γ − LX/L Edd . The anti-and positive correlations between X-ray photon index and Eddington ratio are also found in low-luminosity active galactic nuclei (LLAGNs) and luminous AGNs respectively, where both a single AGN and AGN sample follow these trends (e.g., Wang et al 2004;Shemmer et al 2006;Markowitzet al 2009;Sobolewska & Papadakis 2009;Gu & Cao 2009;Emmanoulopoulos et al 2012;Trichas et al 2013;Allen et al 2015). It should be noted that the anti-and positive correlations are roughly consistent with the prediction of ADAF and disk-corona model respectively (e.g., Yuan et al 2007;Cao 2009;You et al 2012;Qiao & Liu 2013).…”
mentioning
confidence: 95%
“…4 & 5), locates at L X /L Edd ∼ 10 −3 (e.g., Yuan et al 2007;Constantin et al 2009;Veledina et al 2011;Trichas et al 2013). If we take the correction factor between the 2-10 keV X-ray luminosity and the bolometric luminosity L bol to be ∼ 1/16 (Ho 2008), then the turning point is at L bol /L Edd ∼ (1 − 2)%.…”
Section: Turning Point At L X ∼ 10 −3 -Location Of the Transition In mentioning
confidence: 99%